Constituintes químicos de Paliavana tenuiflora Mansf. (Gesneriaceae) - Sales, Kaio Aragão (2015)
Paliavana tenuiflora is a species of the Gesneriaceae family, being composed of about 150 genera with 3.200 species, among herbs, shrubs and small trees. Gesneriaceae species are found in the tropics of all continents, with wide distribution in Brazil, mainly in the Atlantic Forest in the southeast and northeast, totaling 211 species in 27 genera found in the country. There are reports of several classes of secondary metabolites isolated in the family, standing out above all others flavonoids, terpenoids, quinones and the phenolic compounds. Paliavana tenuiflora is found in humid forests on rocky outcrops in Bahia, Minas Gerais, Paraíba e Pernambuco. Due to the existence of only one phytochemical study report with this plant, the present study aimed at searching for secondary metabolites which were not reported yet in this specie, thus contributing with its chemotaxonomy knowledge and enabling the biological activity studies of the compounds found. For this purpose the plant material was collected in Fagundes-PB, and then it was sequentially dried and pulverized, subjected to extraction processes, partition and chromatography techniques to isolate chemical constituents. The chemical structures of the isolated compounds were determined by 1H-NMR and 13C –NMR and by comparison with models reported in the literature. The study led to the isolation and structural characterization of the β-sitosterol and stigmasterol mixture, the presilphiperfolan-9-ol sesquiterpene, the tectoquinone anthraquinone and two naphthoquinones, 7-methoxy-8-hydroxy-α-dunnione and tenuiflorol, which is first reported in the literature and the others substances reported for the first time in the genus Paliavana, contributing thus to its chemotaxonomy.